1962
DOI: 10.1172/jci104657
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Antidiuresis Associated With the Administration of Hydrochlorothiazide to Patients With Vasopressin-Resistant Diabetes Insipidus*

Abstract: Laragh, Heinemann, and Demartini first reported that the administration of chlorothiazide during water diuresis results in an increased rate of solute excretion without significant changes in the rate of urine flow (1,2 repeatedly confirmed (6-13), and the thiazide derivatives have now attained a place of therapeutic usefulness in patients with vasopressinresistant diabetes insipidus (13).Inhibition of solute reabsorption in the distal nephron alone does not account for the antidiuretic effect of the thiazide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
1
5

Year Published

1969
1969
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(78 citation statements)
references
References 24 publications
5
67
1
5
Order By: Relevance
“…Before lithium treatment in the four animals studied, the excretion of ADH ranged from 0. (Earley & Orloff, 1962).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before lithium treatment in the four animals studied, the excretion of ADH ranged from 0. (Earley & Orloff, 1962).…”
Section: Resultsmentioning
confidence: 99%
“…The polyuria does not respond to exogenous ADH in the form of DDAVP but clorexolone does reduce urine volume, apparently acting as it would in diabetes insipidus (Earley & Orloff, 1962). Levy, Forrest & Heninger (1973) gave chlorothiazide to a patient with lithium-induced polyuria and found that this reduced the polyuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism by which thiazide diuretics produce their paradoxic antidiuretic effect in patients or animals with diabetes insipidus is poorly understood. Inhibition of NaCl reabsorption in the distal convoluted tubule alone does not account for the antidiuretic effect of the thiazide diuretics (6).…”
mentioning
confidence: 97%
“…Thiazide diuretics paradoxically decrease urine volume and increase urine osmolality presumably by producing a mild sodium depletion (6). The widely accepted hypothesis suggests that thiazide-induced sodium depletion causes a reduction in distal delivery associated with enhanced fractional water reabsorption in the collecting duct (6,7).…”
mentioning
confidence: 99%